Success Factors in Commercialization of Wing-in-Ground Crafts as Means of Maritime Transport: A Case Study - Kristin Kerem; Kristīne Carjova; Ulla Pirita Tapaninen (Future Transportation)
The wing-in-ground (WIG) effect occurs when air pressure is created beneath a craft moving close to the ground. The pressure created adds upwards lift, resulting in less need for propulsion for moving forward. Over the years, several companies in various countries have developed wing-in-ground crafts—marine vessels, looking like airplane, that operate using the ground effect. However, no commercial routes are currently in operation using such crafts. This article seeks to identify the critical factors that contribute to the successful commercialization of WIG crafts. The study is composed of a literature review, a company comparison and an analysis of one case study close to successful commercialization. The study indicates that the following actions are critical for the commercial success of a company engaged in WIG operations: engaging community, enhancing R&D, establishing a robust technological system and focusing on safety and compliance. It is also noted that technological readiness itself does not guarantee the successful implementation of WIG crafts on commercial routes.